The mediating role of parental attachment in the relationship between parenting styles and identity achievement among secondary and preparatory school students - Shimelis Anley Tizazu; Demeke Wolle Ambaye (Bahir Dar Journal of Education)
The purpose of this research was to examine the mediating role of parental attachment in the relationship between parenting styles and adolescents’ identity achievement. To this purpose, 375 adolescent students were drawn from four secondary and preparatory schools in Debre Markos town using proportional stratified sampling technique. Correlational design was employed to conduct the study. Adapted self-report questionnaires for parenting styles, parental attachment and identity achievement of adolescents were used to collect the data from the respondents. Hence, quantitative data were collected and path analysis via linear regression was employed to determine the path coefficients of the variables under consideration. Based on Baron and Kenney’s requirements of single mediation, simple and multiple linear regressions were made to determine the beta value of the four paths. Furthermore, the existence of significant mediation via parental attachment was tested using Sobel’s z-test for each path diagrams. Hence, the findings indicated that parental attachment positively and partially mediated in the relationship between identity achievement and authoritative parenting style. Authoritarian parenting style had positive and significant direct effect on identity achievement, but the indirect effect via parental attachment was not significant. Parental attachment positively and fully mediated the relationship between permissive parenting style and identity achievement. Future research is recommended to extend the work of this study by further examining the mediating role of parental attachment in the relationship between parenting styles and adolescent identity achievement.